1996
DOI: 10.1111/j.1600-0447.1996.tb10653.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes in patients receiving neuroleptic medication

Abstract: The precise aetiology of sudden death in patients receiving neuroleptic medication is uncertain, but cardiac arrhythmias are a possible cause. We investigated the link between neuroleptic medication and electrocardiographic changes predictive of malignant cardiac arrhythmias. Electrocardiographs were performed on 111 patients receiving neuroleptic medication and on 42 unmedicated controls. Prolonged QTc intervals were more common in the patient sample, but QTc dispersion was not significantly increased. QTc in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 6 publications
2
54
2
1
Order By: Relevance
“…Data regarding the other typical agents are inconclusive, although several other studies have reported QT interval prolongation in patients receiving a variety of typical agents, even at conventional doses (Kitayama et al, 1999;Warner et al, 1996). A study of 65 patients taking antipsychotic drugs from the North East of England reported that only 2 (3%) of patients had a prolonged QT c interval .…”
Section: Drug-induced Qt Prolongationmentioning
confidence: 98%
“…Data regarding the other typical agents are inconclusive, although several other studies have reported QT interval prolongation in patients receiving a variety of typical agents, even at conventional doses (Kitayama et al, 1999;Warner et al, 1996). A study of 65 patients taking antipsychotic drugs from the North East of England reported that only 2 (3%) of patients had a prolonged QT c interval .…”
Section: Drug-induced Qt Prolongationmentioning
confidence: 98%
“…Arrhythmias are primarily a result of alterations in cardiocyte membrane ion transfers, which produce ECG changes; alterations include widening of QRS complexes, which can result in slowed intraventricular conduction, favouring the onset of reentry arrhythmias, ventricular tachycardia or fibrillation, changes in T waves, prolongation of the QT interval, and torsades de pointes (4,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are unrelated to brain receptor binding profiles. What these drugs have in common is an action to prolong cardiac repolarisation via blockade of the delayed rectifier potassium channel (l kr ) within the heart (Yap & Camm, 2000). The cloning of the humaǹ ether-a-go-go' (HERG) gene that encodes for this channel has resulted in studies confirming the specific l kr blocking potential of haloperidol, droperidol, pimozide and sertindole.…”
mentioning
confidence: 95%
“…Although increasing antipsychotic dose has been linked to QT prolongation in psychiatric patients (Warner et al, 1996), other factors may operate, creating high-risk groups who develop QT prolongation and arrhythmias even at low doses. Old age, female gender and pre-existing ischaemic heart disease are all likely to increase risk.…”
mentioning
confidence: 99%